Oocyte Cryopreservation at a Young Age Provides an Effective Strategy for Expanding Fertile Lifespan - Poli, Maurizio; Capalbo, Antonio (Frontiers in Reproductive Health, 2021)
With an upward trend in delaying parenthood, women across the world face increasing risk of age-related infertility and involuntary childlessness. Elective oocyte banking strategies offer women the possibility to protect part of their reproductive potential until personal finances, personal relationship or career have stabilized. Timely collection and cryopreservation of oocytes when they are most competent and chromosomal abnormality rates have not yet escalated, are crucial for achieving high live births through IVF treatment at a later stage. To promote reproductive autonomy, women shall be informed about the decrease in fertility rates that sharply intensifies from the age of 35 and the strategies available to maintain their reproductive potential. Together with this information, women should also recognize the limitations of available strategies including expected live birth rates, costs of the procedures and overall approach performance, which is mainly associated with age at cryopreservation, number of oocytes banked and age at accessing the banked oocytes. Evidence-based statistics are not yet available due to the relatively short period in which oocyte cryopreservation has been offered for elective purposes, and the scarce number of patients returning for accessing their oocytes. However, in order to evaluate the applicability of fertility cryopreservation on a large scale, several theoretical models have been proposed to assess the expected efficacy and overall cost-effectiveness of different oocyte banking strategies. In this article, we review current oocyte cryopreservation methodologies, their applications and outcomes. Moreover, we summarize current evidence regarding known parameters affecting oocyte banking efficacy. Finally, we discuss key points that could play a role in improving access to the service and optimization of oocyte banking frameworks.